Determination of a Wire Heat Temperature under a Pulse-Arc Welding Condition by Means of a Calculation and Graphic Method; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Krampit A. G. Andrey Garoldovich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen